2014
DOI: 10.1007/978-3-642-41375-9
|View full text |Cite
|
Sign up to set email alerts
|

Physical Computation and Cognitive Science

Abstract: About This SeriesStudies in Applied Philosophy, Epistemology and Rational Ethics (SAPERE) publishes new developments and advances in all the fields of philosophy, epistemology, and ethics, bringing them together with a cluster of scientific disciplines and technological outcomes: from computer science to life sciences, from economics, law, and education to engineering, logic, and mathematics, from medicine to physics, human sciences, and politics. It aims at covering all the challenging philosophical and ethic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…This corresponds, to a large extent, to the one described by relatively recent mechanistic accounts of computation (see e.g. Miłkowski 2013;Fresco 2014;Piccinini 2015). What these accounts have in common is that they deny that computational states must be individuated according to their representational or semantic content, thus immediately removing one major objection that CE has historically held towards computationalism.…”
Section: Introductionmentioning
confidence: 62%
“…This corresponds, to a large extent, to the one described by relatively recent mechanistic accounts of computation (see e.g. Miłkowski 2013;Fresco 2014;Piccinini 2015). What these accounts have in common is that they deny that computational states must be individuated according to their representational or semantic content, thus immediately removing one major objection that CE has historically held towards computationalism.…”
Section: Introductionmentioning
confidence: 62%
“…A taxonomy of computation in relation to cognition is provided by Fresco [12], who notes that, depending on the specific kind of "information" used, information-processing accounts of computation may differ greatly. Four main types of information in this context are given: syntactic Shannon information [30], algorithmic information [2], semantic information [1] (a case for using truth values rather than logical probability distributions is made in [11]) and finally instructional information [10,13].…”
Section: Previous Workmentioning
confidence: 99%
“…It may therefore be suggested that an information-processing account that is capable of processing sub-symbolic input and producing behaviour in a probabilistic manner might be better suited for this task. Fresco [12] argues that an account based on Shannon information is better suited for probabilistic computation than one based on algorithmic information, as Shannon information is inherently statistical. The main semantic information-processing models deal with propositions rather than data, which is argued to be problematic in describing general computing systems [12].…”
Section: Computational Modellingmentioning
confidence: 99%
See 2 more Smart Citations